2017
DOI: 10.1080/19475705.2017.1294114
|View full text |Cite
|
Sign up to set email alerts
|

Development of a GIS coastal land-use planning tool for coastal erosion adaptation based on the exposure of buildings and infrastructure to coastal erosion, Québec, Canada

Abstract: This study presents the development of a geographic information system (GIS) land-use planning tool for coastal areas based on the calculated exposure to coastal erosion of buildings and infrastructure. Responding to the needs of land-use planners, who are involved in the project from the beginning, this tool facilitates identification of adaptation solutions based on coastal sensitivity to erosion. All buildings, roads, railways, aqueducts, sewer systems, hiking trails and bicycle routes were mapped at high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Indexes of coastal forcing (CF) consist of [30] significant wave height and storms. Indexes of coastal infrastructure (CI) include [5,58,59] the values of roads, values of buildings and population activity. Indexes of disaster reduction (DR) comprise [24] fiscal revenue and GDP per capita.…”
Section: Assessment Index System and Data Sourcesmentioning
confidence: 99%
See 4 more Smart Citations
“…Indexes of coastal forcing (CF) consist of [30] significant wave height and storms. Indexes of coastal infrastructure (CI) include [5,58,59] the values of roads, values of buildings and population activity. Indexes of disaster reduction (DR) comprise [24] fiscal revenue and GDP per capita.…”
Section: Assessment Index System and Data Sourcesmentioning
confidence: 99%
“…This study uses this range to identify potential losses due to coastal erosion. Previous studies [57,58,[61][62][63] have indicated that the range of erosion is the erosion rate multiplied by time. The average rate of coastal erosion in Xiamen is 1 m/a [51].…”
Section: Calculation and Classification Of Indexesmentioning
confidence: 99%
See 3 more Smart Citations